THE PERCEPTION OF THE SUMBA TRIBE COMMUNITY IN THE USE OF HERBAL INGREDIENTS IN CONTROLLING BLOOD PRESSURE - Yanselmus Delo Ngara; Sirli Mardianna; Arie Jefry Ka’areyono (Universitas Airlangga, 2023)
In the Sumbanese people, the use of herbal ingredients in controlling blood pressure is influenced by people's perceptions. The purpose of this study was to find out how the perceptions of the Sumba people in the use of herbal ingredients in controlling blood pressure. The research approach used in this study was a qualitative descriptive approach with data collection techniques including in-depth interviews with research subjects who met inclusion using the lineal snowball sampling method. The results of research on the Sumbanese community found that herbal ingredients were used in the Sumba community because they were considered to reduce blood pressure and it had become a hereditary tradition in the Sumbanese community to use herbal ingredients to control blood pressure. The type of herbal plant that is often used by the community is soursop leaves with the processing technique of boiling. For future researchers, it is hoped that they can prove scientifically that this herbal plant can be used as a treatment to control blood pressure.